Autoeficácia como componente mediador de aprendizagem de elementos acrobáticos na ginástica para todos e na capoeira - Chiquito, Jaqueline Rodrigues; Bandeira, Tania Leandra; Venditti Júnior, Rubens [UNESP] (My University, 2013)
The study addresses self-efficacy in learning acrobatic elements at Gymnastics for All and Brazilian Capoeira. The methodology consisted of descriptive-qualitative method of research. Questionnaires were applied to seven practitioners of modalities (04 capoeira fighters; 02 gymnastic athletes and 01 practitioner of both of them). The answer formed categories of analysis and it was found that sources of mastery and vicarious experiences plus verbal persuasion are relevant and influence the perception of performance. Fear of injury during practice and preparation of educational pre-sports activities to a better understanding of the task influence the choices and also were indicated. The coach needs to merge with playfulness and motivation, with appropriated levels of challenge to carry out the activities, thus optimizing satisfaction, participation and motivation of athletes.

O estudo aborda a autoeficácia na aprendizagem de elementos acrobáticos na ginástica para todos e capoeira. A metodologia consistiu no método qualitativo-descritivo de pesquisa. Aplicamos questionários a sete praticantes das modalidades (04 de capoeira; 02 de ginástica para todos e 01 praticante de ambas). As respostas formaram categorias de análise e constatou-se que fontes de experiências diretas, vicárias e persuasão verbal são relevantes e influenciam a percepção do desempenho. Medo de lesões durante as práticas, além da elaboração de educativos e pré-desportivos para a melhor compreensão da tarefa, influenciam as escolhas. O técnico precisa mesclar ludicidade e motivação com níveis de desafios adequados à realização das atividades, facilitando assim a satisfação, a participação e motivação dos atletas.
Self-efficacy as mediator component in learning of acrobatic elements in gymnastics for all and brazilian capoeira
Keywords: Self-Efficacy; Perception; Brazilian capoeira; Gymnastic for all (General Gymnastics); Autoeficácia; Percepção; Capoeira; Ginástica para todos (ginástica geral)